The effect of endurance training on addicted women's level of alkaline phosphates who use methadone - Farah Haddadi; Mojgan Jazizadeh-Karimi; Mazhar Rostami Nejad; Saied Sokhtehzari; Amir Hossein Monazami; Mohammad Reza Asad (Islamic Azad University, 2015)
Introduction: Previous studies indicated that endurance exercise is effective to decrease or increase the levels of liver enzymes. The aim of this study was to determine the effect of endurance training on alkaline phosphates (ALP) enzyme in Iranian addicted women with methadone. Methods: Thirty Iranian female addicted prisoners and thirty non-addicted encompassed the sampling. The mean of age, height, weight, %BF, body mass index (BMI), and VO2max of experimental group was 33.8 years, 162.2 cm, 62.2 kg, 33.10, 24.22 kg/m2 and 16.18 ml/kg respectively. The case group was supposed to run with 65% HRmax for 2 weeks (3 sessions in a week and for 25 minutes), 65%-75% HRmax for 3 weeks (3 sessions in a week for 35 minutes) and 75%-85% HRmax for 3 weeks (3 sessions in a week for 40 minutes). The blood samples were collected in amount of 5 ml 48 hours before the first session and after the last session of the protocol. The history of heart and liver diseases or hepatitis was not reported in case group. Results: The level of ALP between case and control group in post-test was not significant. The level of ALP in post-test in contrast with pre-test in both groups was increased but this was not statistically significant in case group (P > 0.05). Conclusion: According to the results, the level of ALP in post-test in experimental group did not change after endurance training. Therefore, the investigation of other factors such as having suitable diet habits, quitting smoking, increasing the period of training is recommended for these types of addicts.